Antioxidant, Anti-Inflammatory and Wound Healing Activities of Cochlospermum planchonii Hook. F. - Fankibe, Nakpane; Kantati, Yendubé T.; Metowogo, Kossi; Kombate, Bignoate; Adi, Kojdo; Itiblitse, Kossitsè; Darré, Tchin; Eklu-Gadegbeku, Kwashie; Aklikokou, Kodjo A. (Journal of Drug Delivery and Therapeutics, 2022)
Objective: The medicinal plant Cochlospermum planchonii Hook.f. is used in the management of various ailments in Togolese pharmacopoeia. In this study, we aimed to evaluate the antioxidant and anti-inflammatory activities of roots and leaves of C. planchonii, and burn wound healing activity of its leaf hydroethanolic extracts in rodents. Materials and Methods: Antioxidant activities were assessed using Phosphomolybdenum assay, 2,2-diphenyl-1-picrylhydrazyl (DPPH) test and the reducing power assay. Visceral pain model, formaldehyde-induced paw edema and vascular permeability test were performed to evaluate anti-inflammatory activities in vivo. Burns were induced in rats by applying on the skin of the dorsal region an aluminum plaque preheated to 100°C for 10 seconds. Animals were treated topically with empty Carbopol gel, C. planchonii leaves extract 2.5 and 5 % in Carbopol gel, and Brulex® (Zinc oxide 15 % cream). Results: C. planchonii extracts exhibited good antioxidant capacities close to standard compound, ascorbic acid. Leaves and root hydroethanolic extracts (1000 mg/kg), compared to control animals, significantly reduced the number of writhings (P<0.001) and the volume of paw edema (P<0.001). Similarly, both roots and leaf extracts at 1000 mg/kg have significantly inhibited vascular permeability by approximately 50% compared to the control group. C. planchonii leaves hydroethanolic extract 2.5 and 5 % in Carbopol enhanced wound healing via significantly increased contraction rates (78.63 ± 1.57 and 79.68 ± 1.48 respectively on day 12, P<0.001), confirmed by histological observations. Conclusion: C. planchonii can promote burn healing due to anti-inflammatory, antioxidant and antimicrobial properties of the plant. Keywords: Cochlospermum planchonii, inflammatory, antioxidant, edema, burn wound